ANALISIS MINAT TRADING ONLINE MAHASISWA MELALUI MANFAAT DAN LAYANAN PADA PT AGRODANA FUTURES - Angelina, Helen; H, Andrea Angel; P, Jonathan Alexander; Widyastuti, Maria (UNIKA Santo Thomas, 2024)
Technological developments in this decade have made online trading increasingly popular, especially among young people, namely students, where they can invest with minimal capital and learn to understand global economic developments. PT Agrodana Futures as a verified company can be a forum for students to invest early on. This research also aims to analyze the influence of independent variables in the form of benefits and services on students' online trading interest. The population in the study were UKDC students with a sample of 50 active students majoring in UKDC management. The type of research used is quantitative research using a questionnaire as a research instrument. The sampling technique used is non-probability sampling or objective sampling. In this research, data processing uses SPSS version 25. Based on the results of data processing, it is said that all statement items are declared valid and all variables are declared reliable, and the classical assumption test is met. Based on the T test results, it can be concluded that services and benefits have a significant influence on student interest in Online Trading.